2009
DOI: 10.1186/1472-698x-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of modifiable risk factors of Coronary Atherosclerotic Heart Disease (CASHD) among a sample in India

Abstract: BackgroundThe prevalence of Coronary Atherosclerotic Heart Disease (CASHD) is increasing in India. Several modifiable risk factors contribute directly to this disease burden. Public knowledge of such risk factors among the urban Indian population is largely unknown. This investigation attempts to quantify knowledge of modifiable risk factors of CASHD as sampled among an Indian population at a large metropolitan hospital.MethodsA hospital-based, cross sectional study was conducted at All India Institute of Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
22
5
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 10 publications
14
22
5
2
Order By: Relevance
“…Regarding the presence of hypertension and diabetes, 16.2% and 9.2% of the total respondents had hypertension and diabetes respectively which is congruous with the study done by (Saeed et al;2009) which showed 8.9 % hypertension, 6.6% diabetes. Similarly, another study done in Pakistan by 2005) showed that 14.9 % had hypertension and 5.9 % had diabetes respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Regarding the presence of hypertension and diabetes, 16.2% and 9.2% of the total respondents had hypertension and diabetes respectively which is congruous with the study done by (Saeed et al;2009) which showed 8.9 % hypertension, 6.6% diabetes. Similarly, another study done in Pakistan by 2005) showed that 14.9 % had hypertension and 5.9 % had diabetes respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Jafary et al (2005) found that the education level, income and residence are positively associated with the knowledge on CHD in Pakistan. Similar studies in India and Jordan indicated the same association [18,19]. Yahya et al (2012) found positive association between knowledge, attitude and practice independent of socio-demographic factors among female patients in primary care clinic in Kelantan-Malaysia.…”
Section: Introductionmentioning
confidence: 69%
“…3 Hypertension is now a burden to the society and several modifiable risk factors contribute directly to this burden. 4 High job strain has been associated with significantly higher diastolic blood pressure of 4.5mmHg during working hours 5 and it has been proven that chefs showed one risk factor more than office workers. 6 There is also a dearth of information on diet related chronic diseases in West Africa creating a challenge for comparative research for intervention purposes.…”
Section: Introductionmentioning
confidence: 99%